PENGARUH KEPERCAYAAN MEREK, KESADARAN MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE XIAOMI DI DIY - Isnan Rizki Khoirudin; Eko Giyartiningrum (Program Studi Manajemen, 2021)
This study aims to determine the effect of brand trust, brand awareness and product quality on purchasing decisions for Xiaomi smartphones for all consumers of Xiaomi smartphone users in Yogyakarta. The population used in this study were all consumers who use Xiaomi smartphones in Yogyakarta, with a sample of 100 respondents. The sampling technique used nonprobability sampling with a purposive sampling approach. The data collection technique used a questionnaire. The data analysis method used is multiple linear regression analysis, classical assumption test, hypothesis testing. The results of this study indicate that brand trust and product quality partially influence purchasing decisions. Brand trust, brand awareness and product quality simultaneously influence purchasing decisions.